PENGARUH MODEL PROJECT BASED LEARNING (PJBL) DENGAN MENGGUNAKAN MEDIA KONKRET UNTUK MENINGKATKAN MINAT BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMPN 3 KOPANG - Ela Putri Adekayanti; Masjudini; Sri Yulianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to determine the extent to which the use of the Project Based Learning (PJBL) model combined with concrete media influences the learning interest and mathematical problem-solving abilities of seventh-grade students at SMPN 3 Kopang. The research was motivated by the low level of learning interest and the suboptimal problem-solving skills of students in algebra, as identified through initial observations and learning-interest questionnaires. This study employed a quantitative approach using a quasi-experimental design in the form of a Pretest–Posttest Control Group Design, with the sample selected through purposive sampling, resulting in class VIID as the experimental group and class VIIB as the control group, each consisting of 25 students. The instruments used included a learning-interest questionnaire and a problem-solving test. The findings indicate that the implementation of PJBL supported by concrete media had a significant effect on increasing students’ learning interest, as shown by the rise in the experimental class’s average score from 56.9 to 95.3, while the control class decreased from 57.95 to 55.1, with a Sig. value of 0.000 < 0.05 based on the independent sample t-test. In addition, the model also had a significant impact on students’ problem-solving abilities, evidenced by an increase in the experimental class’s average score from 14.2 to 79.2, whereas the control class remained at 11.4, with a Sig. value of 0.000 < 0.05 on the Mann–Whitney U test. Overall, the application of PJBL accompanied by concrete media proved effective in enhancing students’ learning interest and mathematical problem-solving skills.